Promoting social communication in high functioning individuals with autistic spectrum disorders - Paul, Rhea (Child and Adolescent Psychiatric Clinics of North America, 2003)
This article reviews a range of social communication interventions that have been developed for students with autism at the preschool, school age, and adolescent level. Adult-mediated and peer-mediated methods that use highly structured, child-centered, and hybrid methods are examined. Programs that provide information on generalization and maintenance are identified. A set of recommendations for programs that would seem to be most appropriate for students with Asperger syndrome is presented.
Keywords: *Asperger Syndrome/th [Therapy]; *Autistic Disorder/th [Therapy]; *Intelligence; *Social Behavior; Adolescent; Asperger Syndrome/di [Diagnosis]; Asperger Syndrome/px [Psychology]; Asperger syndrome; Autistic Disorder/di [Diagnosis]; Autistic Disorder/px [Psychology]; Behavior Therapy; Child; Child, Preschool; Humans; Peer Group; Play and Playthings; Social Adjustment; adolescent; adult; autism; child; child psychiatry; dept.cmd; human; interpersonal communication; peer-reviewed; priority journal; review; school; social adaptation; social interaction; training; verbal communication

Management of children with APDs - Jirsa, Robert E (The Hearing journal, 2003)
The management of children with auditory processing disorders requires a multifaceted approach involving audiologists, speech-language pathologists, and educators. We are still at the genesis of our understanding of APDs.
Keywords: accuracy; association; audiology; auditory discrimination; auditory nervous system; auditory stimulation; auditory system examination; auditory system function; child; child behavior; child care; computer program; dept.cmd; frequency modulation; health care planning; hearing disorder; human; interpersonal communication; medical specialist; note; school; sensory system electrophysiology; signal noise ratio; signal processing; task performance; technology; writing

Clinical issues: Asperger Syndrome: the role of speech-language pathologists in schools - Paul, Rhea; Sutherland, Dean (Perspectives on Language Learning and Education, 2003)
Keywords: dept.cmd